Comparison of Sudden Sensorineural Hearing Loss with Tinnitus and Short-Term Tinnitus - Fang Qi; Liang Chaoqun; Yan Lin; Yang Jianming (Neural Plasticity, 2021)
Objective. As one of the common symptoms of sudden sensorineural hearing loss (SSH), tinnitus seriously affects the life and work of SSH patients. The present study is aimed at exploring whether SSH can receive acoustic therapy and the factors that affect the efficacy of SSH acoustic therapy. Methods. A total of 162 patients were outpatients and inpatients, 86 were SSH, and 76 were short-term tinnitus (STT). Both groups received pure tone audiometry, tinnitus matching, and residual inhibition test (RI). The Tinnitus Handicap Inventory (THI), visual analog scale with respect to tinnitus loudness (VAS), and RI in each group were evaluated. The effects of age, degree of hearing loss, and tinnitus course on the efficacy of SSH acoustic therapy were also evaluated. Results. In the comparison of RI, THI, and VAS, there was no difference between SSH and STT (P>0.05). SSH patients with mild hearing loss showed better acoustic therapy efficacy compared with SSH patients with severe hearing loss (P<0.05), but there is no statistical difference in age and the course of tinnitus (P>0.05). Conclusion. The present study showed that SSH may improve tinnitus symptom through receiving acoustic therapy and SSH patients with mild hearing loss can get better acoustic therapy effects.